2017
DOI: 10.1002/pen.24542
|View full text |Cite
|
Sign up to set email alerts
|

A novel poly(vinylidene fluoride) composite membrane for catalysis and separation

Abstract: Timely separation of products from the reactant is a great challenge for a catalytic reaction process. In this study, we fabricated a novel poly(vinylidene fluoride) composite membrane with noble metal (Au, Ag, and Pd) nanoparticles in membrane pores to solve the faced challenge. The composite membrane has a unique structure comprising membrane surfaces with only PVDF and membrane pores with poly(methacrylic acid) microspheres coated by noble metal nanoparticles. The composite membrane is used for the catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“…The morphology analysis showed that blending 1–3 wt% PVAc in PEI produces stable blend membranes. Dense membranes are always preferred for gas separation over porous membranes because the separation performance of dense membranes is better than porous membranes .…”
Section: Resultsmentioning
confidence: 99%
“…The morphology analysis showed that blending 1–3 wt% PVAc in PEI produces stable blend membranes. Dense membranes are always preferred for gas separation over porous membranes because the separation performance of dense membranes is better than porous membranes .…”
Section: Resultsmentioning
confidence: 99%
“…No scientific work of this compound has been reported in gas separation. However PVDF was extensively investigated as membrane in other areas of membrane processes . Considering some published papers on GO containing MMMs, it can be concluded that GO with high aspect ratio is an inspiring filler for efficient MMM construction in practical gas separation application.…”
Section: Introductionmentioning
confidence: 99%
“…PVDF has been extensively used as a membrane material due to its outstanding chemical, thermal, and mechanical properties, the significantly high hydrophobicity and the thermodynamic compatibility with other polymers which makes possible further chemical modifications to induce tailor made functions . Thus, except from being widely used in conventional filtration processes (micro and ultrafiltration), PVDF membranes are lately regarded as potential candidates for membrane contactor, membrane reactor and membrane distillation processes . Most of the asymmetric PVDF membranes are produced by the immersion‐precipitation (IP) method due to the simplicity of the process and the ease of PVDF dissolution in a range of organic solvents, while nonsolvent‐induced phase separation processes are also applied .…”
Section: Introductionmentioning
confidence: 99%